Population structure and genetic diversity of Bromus tectorum within the small grain production region of the Pacific Northwest. Issue 20 (7th September 2017) - Lawrence, Nevin C.; Hauvermale, Amber L.; Dhingra, Amit; Burke, Ian C.
Abstract: Bromus tectorum L. is an invasive winter annual grass naturalized across the United States. Numerous studies have investigated B. tectorum population structure and genetics in the context of B. tectorum as an ecological invader of natural areas and rangeland. Despite the wealth of information regarding B. tectorum, previous studies have not focused on, or made comparisons to, B. tectorum as it persists in individual agroecosystems. The objectives of this study were to assess the genetic diversity and structure, the occurrence of generalist and specialist genotypes, and the influence of climate on distribution of B. tectorum sourced exclusively from within small grain production regions of the Pacific Northwest. Genetic diversity of B. tectorum sourced from agronomic fields was found to be similar to what has been observed from other land use histories. Six distinct genetic clusters of B. tectorum were identified, with no evidence to indicate that any of the genetic clusters were better adapted to a particular geographical area or climate within the region. Given the apparent random spatial distribution of B. tectorum genetic clusters at the spatial scale of this analysis, unique genotypes may be well mixed within region, similar to what was reported for other inbreeding weedy grass species. Abstract : Despite the wealth of information regarding Bromus tectorum population genetics, previous studies have not focused on, or made comparisons to, B. tectorum as it persists in individual agroecosystems. The objectives were to assess the genetic diversity and structure, the occurrence of generalist and specialist genotypes, and the influence of climate on distribution of B. tectorum sourced exclusively from within small grain production regions of the Pacific Northwest. Given the apparent random spatial distribution of B. tectorum genetic clusters at the spatial scale of this analysis, unique genotypes may be well mixed within region, similar to what was reported for other inbreeding weedy grass species.